Penguatan Infrastruktur Mikro di Zona Bozem Kampus UPN “Veteran” Jawa Timur Melalui Rancang Bangun, Monitoring, danEdukasi Publik - Suwardana, Romy Trizki; Pradanarka, Andyas Mukti; Erlangga, Achmad Fadli; Oktavia, Dini; Permana, Febrian Raditya (Fakultas Teknik Universitas Bhayangkara Jakarta Raya, 2025)
This community service program (KKN) at the campus lake of UPN “Veteran” East Java aimed to strengthen micro-infrastructure through design-build activities, monitoring, and public education. Activities included site surveys, repainting pedestrian paths, installing solar street lamps, and creating plant identification and informational signage. A participatory field approach was applied, involving students, campus stakeholders, and simple performance indicators such as coverage of works, functioning rate of installed lamps, and community engagement in outreach. Results demonstrated improved aesthetics and safety of pedestrian routes, operational solar lighting, and informative signage that enhances environmental awareness. Active student–community interaction fostered collective responsibility for site maintenance. In conclusion, the micro- infrastructure interventions proved effective in improving public-space functionality and can serve as a scalable model for sustainable campus ecosystem management.